An Automaton-based Index Scheme for On-demand XML Data Broadcast - SUN, Weiwei (Institutional Knowledge at Singapore Management University, 2012)
XML data broadcast is an efficient way to deliver semi-structured information in wireless mobile environment. In the literature, many approaches have been proposed to improve the performance of XML data broadcast. However, due to the appearance of wildcard ”*” and double slash ”//” in queries, their performance deteriorates. Consequently, in this paper, we propose a novel air indexing method called Deterministic Finite Automaton-based Index (abbreviated as DFAI) on the XPath queries. Different from existing approaches which build index based on XML documents, we propose to build the index based on the queries submitted by users. The new index treating the XPath queries with ”*” or ”//” as a DFA actually improves the efficiency of broadcast system significantly. We further propose an efficient compression strategy to reduce the index size of DFAI as well. Experiment results show that our new index method achieves a much better performance in terms of both access time and tuning time when compared with existing approaches.